Perancangan Aplikasi Game Edukasi Berbasis Android Menggunakan Mit App Inventor Sebagai Media Pembelajaran TIK di SMPN 03 Sungai Pua - Syukra, Annisa Jannatul; Zakir, Supratman; Ilmi, Darul; Efriyanti, Liza (Journal of Information System and Education Development, 2023)
ABSTRACKThis research is motivated by Japanese language lessons. The results of interviews with teachers of Japanese subjects at SMKN 4 Payakumbuh that the media used are modules, and blackboards that do not fully support learning, using conventional methods or lectures, students' knowledge of foreign language vocabulary is low, students' learning motivation is low and less variety of media used. Meanwhile, students said that Japanese lessons are quite difficult to remember the vocabulary and the media used are modules and blackboards where the modules given to students cannot be taken home only to be studied in class, so many students have learned vocabulary in class when they arrive. At home, many of them forget the vocabulary they have learned. Based on this, the solution given is to design an interesting learning educational game. The researcher provides a solution by providing a technological approach, namely producing an Educational Game Design for Class X Japanese Language Lessons by Using the Educandy Application at SMKN 4 Payakumbuh.